Integration of Waqf and Islamic microfinance for poverty reduction in OIC Member Countries: a case study of Nigeria - Haneef, Mohamed Aslam; Pramanik, Ataul Huq; Mohammed, Mustafa Omar; Muhammad, Aliyu Dahiru; Amin, Fouad Md (The Islamic and Training Research Institute (IRTI), 2019)
Microfinance was celebrated in the year 2005 as an effective tool for poverty reduction. However, until now, the penetration of microfinance into the mainstream financing is very shallow and its total share to global credit falls below 1 percent. The private investment in the industry reaches 7.5 billion USD. Yet, significant number of poor micro-entrepreneurs is yet to be reached globally. This may not be unconnected with the ―one size fits all solution‖ approach of microfinance. Hence, the need for Islamic microfinance dominates the agenda of many Muslims countries today. Despite the rapid growth in the domestic market, with GPD growth rate of 7 percent in 2013, making it the largest economy in Africa, Nigeria remains prone to poverty and food insecurity that destabilize ordinary citizens and their survival. The celebrated microfinance has not helped much in Nigeria. In fact, out of the 900 microfinance banks in the country, more than 200 were shut down by the apex bank due to misappropriation of deposits and gross violation of the CBN guidelines. The objective of this study is to propose an integrated waqf based Islamic microfinance that is Sharia compliant and capable of harnessing the huge waqf sector to support Islamic microfinance and subsequently overcome shortage of capital faced by microfinance in the country. The study employs survey technique to collect data from 248 respondents from Kano State Zakāh and Hubsi Commission and Grassroots Microfinance Bank based in Kano. The data was analyzed using structural equation modeling. The findings show that all the factors used have high Cranach alpha with minimum of 0.7. The hypotheses tested were all accepted at 5 percent significance level. The implication of the study is that waqf resources can be channeled through Islamic microfinance to improve the welfare of the clients, solve their capital need and human resource deficiency. Keywords: Waqf, Islamic Microfinance, Integration, poverty reduction, Nigeria 1. Introduction Nigeria is a resource-rich country with huge population of almost 170 million as at 2014. This huge endowment of both human and natural resources coupled with vast agricultural land, puts the country in an advantageous position in the Sub-Saharan Africa. One fact however remains visible—the high incidence of poverty as the majority of the population falls below $1.25USD